Community health worker empowerment through collaborative models with community midwifery - Arlina Dewi; Supriyatiningsih Supriyatiningsih; Sri Sundari; Dianita Sugiyo; Dyah Tri Kusuma Dewi (Intelektual Pustaka Media Utama, 2023)
From 2007 to 2015, Indonesia’s maternal mortality rate (MMR) increased from 228/100,000 to 305/100,000 live births. The government has established a policy to reduce the MMR in rural and remote areas, which includes the maternal waiting home (MWH) program and the placement of community midwifery. However, the use of MWH in Indonesia, such as in South Sulawesi Province, remains low. This study aimed todetermine the impact of the community health worker (CHW) Empowerment Collaboration Model on the use of maternal waiting home (MWH). This was a quasi-experimental study with a control group and pre-post test design. This investigation was conducted at four community health centers in Bulukumba, South Sulawesi. A total of 125 pregnant women were selected for the study and divided into two groups: 66 in the experimental group and 59 in the control group. The collaborative empowerment model for CHWs was implemented in five stages. CHW provided the experimental group with education. In the experimental group, there were statistically significant increases in knowledge, attitude, and MWH use, whereas there were no statistically significant increases in the control group. Community health worker empowerment with a collaboration model significantly improves pregnant women's knowledge, attitudes, and MWH utilization outcomes (210%).